Characteristics of Cases With Repeated Sexually Transmitted Infections, Massachusetts, 2014–2016. (13th January 2018) - Hsu, Katherine K; Molotnikov, Lauren E; Roosevelt, Kathleen A; Elder, Heather R; Klevens, R Monina; DeMaria, Alfred; Aral, Sevgi O
Abstract : Of Massachusetts residents 13-65 years, 1% were reported with at least one bacterial STI in 2 years; 14.2% of those reported had ≥2 STIs and accounted for 27.7% of STIs reported, implying repeat infections have disproportionate impact on STI rates. Abstract: Background: Persons with prior sexually transmitted infections (STIs) are at high risk for reinfection. No recent studies have examined frequency with which persons are diagnosed and reported with multiple bacterial STIs over time. Methods: We conducted a retrospective, of confirmed syphilis, gonorrhea, and chlamydial infections reported to Massachusetts state surveillance system within a 2-year period, 28 July 2014–27 July 2016. Results: Among Massachusetts population aged 13–65 years (4847510), 49142 (1.0%) were reported with ≥1 STIs; 6999 (14.2% of those with ≥1 STI) had ≥2 STIs, accounting for 27.7% of STIs. Of cases with ≥5 or more STIs (high-volume repeaters), 118 (74%) were men and 42 (26%) were women. Men spanned the age spectrum and were predominantly non-Hispanic white; 87% reported same-sex contacts. Women were younger, predominantly nonwhite, and without known same-sex contacts. Women were reinfected with gonorrhea and chlamydia or chlamydia alone; none had syphilis or human immunodeficiency virus (HIV) infection. All men with syphilis also had gonorrhea and/or chlamydia; 35% were diagnosed with HIV before, during, or within 10 months after study period. The majority (56%) of high-volume repeaters were seen at more than 1 care site/system. Conclusions: In Massachusetts, a large proportion of bacterial STIs are reported from a small subpopulation, many of whom have repeated infections and are likely to have higher impact on STI and HIV rates. Public health can play a crucial role in reaching high-volume repeaters whose STI histories may be hidden from clinicians due to fragmented care.